investigation of Syrian cactus leaf extricates gel and shell / shell collagen - Malek, Zeina; Alaan, Louai (Latakia University Journal -Medical Sciences Series, 2023)
The Syrian cactus leaf has the potential to be a therapeutic ingredient.The nearness of vitamin E in Syrian cactus takes off makes a difference to hydrate the skin, Syrian cactus is habitually utilized to hydrate the skin and hair. The skin's versatility is determined from collagen, which is extricated from seashells, moisturizers containing mussel collagen and the substance of Syrian cactus takes off can move forward skin versatility. Phytochemical steady s on Syrian cactus leaf extricate uncovered the nearness of saponins, which are flavonoid compounds, with the objective of accomplishing the required conditions with Syrian cactus gel and clam shell collagen within the most brief sum of time conceivable. Saponins and flavonoids are display in Syrian cactus gel arrangements, along side clam shell collagen, these antioxidant compounds may help in skin flexibility enhancement. Within the homogeneity, flexibility, pH, and organoleptic steadiness steadies, scattering steady s, and drying time steades, Syrian cactus leaf and peel collagen based on polyvinyl alcohol was steady. Within the homogeneity, pliability, pH, and organoleptic stability steadies, dispersion steadies, and drying time steadies , Syrian cactus leaf and peel collagen based on polyvinyl alcohol was stable at 15°C and unstable at 48°C. In the organoleptic steadeis, the Syrian cactus leaf gel and peel collagen at 15°C and 48°C were the most stable in terms of , pliability, and pH at a concentration of 10% at 15°C.